Comparison of predictive value of CRB 65 and SMART COP in patients with community acquired pneumonia presenting in emergency ward at tertiary care hospital in eastern Nepal - Gajmer, Raj Kumar; Giri, Rajani; Giri, Saroj; Jirel, Sunil; Thapa, Jeevan; Bhandari, Rabin (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Introduction: Pneumonia, a common emergency presentation presents in variable clinical urgency making decision tools useful. We aimed to compare two of such scores, CRB 65 and SMART COP to predict 30 days’ mortality and intensive care requirement. Method: A comparative observational study was done among 330 patients. CRB 65 and SMART COP scores were calculated and patients were followed up till the outcome of interest. Sensitivity, specificity, negative and positive predictive value were calculated at different cut offs for both the scores with 95% significance level and ROC curves were plotted with measure of Area under the curve (AUC). Result: Three hundred thirty patients were evaluated for mortality, and 287 patients for ICU admission after loss to follow up and incomplete information. The mean ± SD age of patient was 59.41±20 years with mortality in 24.8% (including 4 mortality cases in emergency). ICU admission was required among 7% of patients. For predicting 30 days’ mortality, the AUC of CRB 65 was 0.669, while that of SMART COP was 0.765 and the difference was statistically significant (p-value= 0.045). Similarly for predicting ICU admission, the AUC of CRB65 was 0.831 and that for SMARTCOP was 0.783 (p-value = 0.552). For both 30 days mortality and ICU admission, maximum sensitivity and specificity was obtained for cut-off of 2 for CRB65 and 7 for SMARTCOP. Conclusion: CRB 65 was found to be equally capable of predicting need of ICU admission as by the SMART COP tool. It was also found to have good predictability of 30 days mortality with high sensitivity and specificity. Thus, it can be the useful tool in low resource setting for inpatient management or early referral.